2015
DOI: 10.1515/ejnm-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Surface modified Mg-doped ZnO QDs for biological imaging

Abstract: Nanocrystals of ZnO are currently attracting great interest as potential labels for biological applications, such as theranostic devices, due to their luminescent properties and low toxicity in vivo. It has been reported that doping with Mg 2+ ions could enhance the luminescence of ZnO quantum dots (QDs). In the present study Mg-doped ZnO QDs were synthesized by a hydrolysis and condensation reaction. Surface modification of the QDs was performed using oleic acid (OA) to hinder their aggregation and to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
4
12
1
Order By: Relevance
“…QY results showed that the surface modifiers do not interfere significantly when compared to the ZnO-QDs colloidal suspension (10.2%), which corroborated with the QY reported by Manaia et al [36]. The results related with ZnO-QDs capped by GPTMS and HTMS can be explained by reduction of defects present in the crystal structure (as seen above).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…QY results showed that the surface modifiers do not interfere significantly when compared to the ZnO-QDs colloidal suspension (10.2%), which corroborated with the QY reported by Manaia et al [36]. The results related with ZnO-QDs capped by GPTMS and HTMS can be explained by reduction of defects present in the crystal structure (as seen above).…”
Section: Resultssupporting
confidence: 89%
“…The lower photoluminescence intensity in the yellow spectral range for bare ZnO-QDs probably occurred during acquisition of the ZnO-QDs in powder form. The above results are different from that found for the ZnO-QDs colloidal suspension prepared by sol-gel route, which having shown a great photoluminescence in the green spectral range [36]. This phenomenon might be related with the security of NPs in function of colloidal protection, which is lost after the ZnO-QDs powder obtaining.…”
Section: Resultscontrasting
confidence: 72%
“…Moreover, the luminescence of ZnO nanocrystals can be improved or modulated by doping the structure with other ions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are used in a wide range of applications such as photocatalysts, sensors, electroluminescent devices and lasers [ 1 , 2 , 3 , 4 ]. More specifically, ZnO quantum dots (QDs) are promising luminescent probes for bioimaging due to their biodegradability and very low toxicity in vivo [ 5 , 6 , 7 , 8 , 9 ]. In recent years, ZnO/ZnS heterostructures have emerged as an attractive approach for tailoring the particle characteristics and properties [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%